Apo View Hotel employees' perceptions on the use of internal public relations strategies as antecedent of its organizational communication a case study - More, Shimea Joy M.
Apo View Hotel has become one of the pioneering organizations in the service industry in Davao City. For more than sixty years it has established its identity as one of the topmost destinations of tourist accommodations. It is run by traditions that have well suited the needs of its external audience. This being said, is one of the products of good internal relations within the organization. In line with this, the researcher was interested in studying the communication that exists between the employees and the organization as a whole. Specifically, the use of internal relations tools in the context of a business organization, i.e. hotel, is the primary focus of this study which aims to define the lines of communication within in Apo View Hotel. It utilized surveys and interviews as a means of acquiring the necessary data to achieve the objectives and the variables of this study were employees? perceptions towards the public relations tools. Their satisfaction rate were obtained, to know whether the current tools were efficient in maintaining the fluidity of communication inside the organization and whether these tools were helpful in facilitating employee relationships. The uses and Gratifications Theory by Blumler and Katz was applied as to provide a solid grounding for this study. The results were interpreted based on the computed frequency and percentage of responses. The results showed that employees are highly satisfied with regards to the usefulness of the current internal public relations tools. Primarily, Apo View has been utilizing meetings and memoranda to disseminate organizational messages. Based on the employees? responses, it demonstrated that the organization puts a high emphasis for upward communication which is characterized from the usage of the tools that were mentioned. Also, the results of the identified certain factors that affected employees? perception on the usefulness of the tools such as the length of time that an organization need not apply a wide variety of public relations tools to supply information among the employees. Constant updating and proper management are more important factors for maintaining organizational relationships.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication